Age and growth of the sand lobster Thenus orientalis (Lund) from Bombay waters - Kagwade, P V; Kabli, L M (Indian Journal of Fisheries, 2011)
Age of the sand lobster Thenus orientalis was determined by length frequencydistributior. using scatter diagram technique. Growth rates of males andfemales were identical till the first 2 years after which the former recordedhigher rate of growth. Males upto 3 and females upto 4.5 years contributedto the com:nercial trawl catches. Growth parameters estimated by the vonBertalanffy's growth equation were: L = 368 mm, K = 0.1279 and T =-0.7368 for males and L = 300 mm, K = 0.1690 and T = -0.7 for fem~les.The growth pattern wa; retrogressive geometric throughout the life in thisspecies.